2020
DOI: 10.1002/htj.21924
|View full text |Cite
|
Sign up to set email alerts
|

Transient free convection of a second‐grade fluid flowing in a vertical cylinder

Abstract: The intention of the present article is to examine the transient effect on the free convection of the second‐grade fluid flowing in a vertical cylinder. We have found the analytical solution of the derived governing partial differential equations in nondimensional form corresponding to the velocity as well as the temperature fields by applying the Laplace transformation method in terms of the Bessel function of the first kind. To obtain the impacts of the appropriate parameters related to the given equations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The authors found that the velocity and temperature distribution decreases when the suction/injection parameter increase. Recently, Dwivedi et al, [27] acknowledged the transient effect of a second-grade fluid flows past a vertical cylinder. The research output indicated that the velocity profiles and the mass flow rate were dismissed by the second-grade fluid parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the velocity and temperature distribution decreases when the suction/injection parameter increase. Recently, Dwivedi et al, [27] acknowledged the transient effect of a second-grade fluid flows past a vertical cylinder. The research output indicated that the velocity profiles and the mass flow rate were dismissed by the second-grade fluid parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The second-grade model has almost the same as the model of Walter-B fluid which involves viscosity and elastic properties but the second-grade model involves two derivatives in the stress-strain tensor relationship. Besides, the second-grade fluid has a wide application in polymer processing industries, power engineering, petroleum production, and chemical engineering [27,28]. In addition, the study of fluid flow with the effect of wall transpiration has got attracted many people due to its application.…”
Section: Introductionmentioning
confidence: 99%